Efficient Synthesis of D‐Phenylalanine from L‐Phenylalanine via a Tri‐Enzymatic Cascade Pathway. Issue 13 (1st June 2021) - Lu, Cui; Zhang, Sheng; Song, Wei; Liu, Jia; Chen, Xiulai; Liu, Liming; Wu, Jing
Abstract: D‐phenylalanine is an important intermediate in food and pharmaceutical industries. Here, to enable efficient D‐phenylalanine biosynthesis from L‐phenylalanine, a tri‐enzymatic cascade was designed and reconstructed in vivo . The activity of Proteus vulgaris meso‐diaminopimelate dehydrogenase (PvDAPDH) toward phenyl pyruvic acid was identified as the limiting step. To overcome, the tension in the phenyl pyruvic acid side‐chain, PvDAPDH was engineered, generating PvDAPDH W121A/R181S/H227I, whose catalytic activity of 6.86 U mg −1 represented an 85‐fold increase over PvDAPDH. Introduction of PvDAPDH W121A/R181S/H227I, P. mirabilis L‐amino acid deaminase, and Bacillus megaterium glucose dehydrogenase in E. coli enabled the production of 57.8 g L −1 D‐phenylalanine in 30 h, the highest titer to date using 60 g L −1 L‐phenylalanine as starting substrate, which meant a 96.3 % conversion rate and >99 % enantioselectivity on a 3‐L scale. The proposed tri‐enzymatic cascade provides a novel potential bio‐based approach for industrial production of D‐phenylalanine from cheap amino acids. Abstract : Enzymatic Cascade : D‐Phe is an important intermediate in food and pharmacy. In this study, we constructed a tri‐enzymatic cascade reaction for the generation of D‐Phe from cheap L‐Phe, employing the enzymes LAAD, DAPDH and GDH. Limited by poor catalytic efficiency of DAPDH, PPA intermediate was found accumulated when producing D‐Phe in whole‐cell system. We improved its activity towards PPA by protein engineering. By integrating the best DAPDH variants into the system and further duplication of the LAAD gene, we approached to the optimal activity ratio among LAAD, DAPDH and GDH and realized high production of D‐Phe.